2005
DOI: 10.1149/1.1951205
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Hafnium Silicate Gate Dielectric Films Using Hf[N(CH[sub 3])(C[sub 2]H[sub 5])][sub 4] and SiH[N(CH[sub 3])[sub 2]][sub 3] Precursors

Abstract: Hf-silicate gate dielectrics were formed by atomic layer deposition ͑ALD͒ technology using the liquid Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 and SiH͓N͑CH 3 ͒ 2 ͔ 3 precursors. The advantages of these precursors as good materials is because their melting points and vapor pressures are in a comfortable working range. In SiO 2 ALD film formation, the growth rate per cycle was dependent on reactor pressures between 0.5 and 5.0 Torr chamber pressure. In order to obtain a good uniformity of less than 5%, the pressures of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…Of the deposition techniques used for high-k films [10][11][12][13][14][15][16][17][18][19][20], atomic layer deposition (ALD) technology is desirable for precise control of the composition, film thickness, conformality and uniformity. Hafnium-tetrachloride (HfCl 4 ) and water (H 2 O) have been widely used for depositing HfO 2 using ALD [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the deposition techniques used for high-k films [10][11][12][13][14][15][16][17][18][19][20], atomic layer deposition (ALD) technology is desirable for precise control of the composition, film thickness, conformality and uniformity. Hafnium-tetrachloride (HfCl 4 ) and water (H 2 O) have been widely used for depositing HfO 2 using ALD [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…And, ALD process temperature about 275°C have been suitable for the fabrication of ultrathin HfO 2 gate dielectrics to improve the leakage current characteristics due to formation of low residual impurity concentrations such as carbon [18]. However, there have been few papers on the subject of Hfsilicate gate dielectrics using the ALD method because of the lack of a suitable Si precursor [19,20]. In this study, we investigated SiO 2 layers using Bis-dimethylamino-silane (BDMAS: SiH 2 (N(CH 3 ) 2 ) 2 ) and Tris-dimethylamino-silane (TDMAS: SiH(N(CH 3 ) 2 ) 3 ) precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Atomic layer deposition ͑ALD͒ is desirable for precise control of composition, film thickness, conformity, and uniformity among many high-k film deposition techniques. [8][9][10][11][12][13] Hafnium-tetrachloride ͑HfCl 4 ͒ and water ͑H 2 O͒ were widely used for ALD HfO 2 film formations. 8,9 Recently, there were reports using Hf-amide-type precursors such as Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 for ALD of HfO 2 or Hf-aluminate films to solve the problem of particle formation with HfCl 4 precursors.…”
mentioning
confidence: 99%
“…11 A tetrakis͑ethylmethylamino͒hafnium ͕Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 ͖ precursor is a good material because the melting point is very low ͑less than −70°C͒ to maintain the middle vapor pressure ͑4.8 Torr at 120°C͒. 12 The ALD process temperature of 275°C was very important for the fabrication of high-quality HfO 2 gate dielectrics to improve the leakage current characteristics using Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 and O 3 . 13 Metal-gate and high-k dielectric transistors can be fabricated by using the damascene gate process 14 and the replacement gate process.…”
mentioning
confidence: 99%
“…9,10 There have been reports of groups using Hf amide-type precursors such as Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 for growing HfO 2 or Hf-aluminate films in order to solve the problem of particles that occurs when using HfCl 4 precursors. [11][12][13][14][15][16] Furthermore, SiH͓N͑CH 3 ͒ 2 ͔ 3 and SiH 2 ͓N͑CH 3 ͒ 2 ͔ 2 precursors are interesting materials because their melting points are very low ͑less than −90°C͒ and they exhibit high vapor pressures ͑92 and 512 Torr at 80°C, respectively͒. 15,16 It has been reported that the thickness and Hf/͑Hf + Si͒ composition ratios of ALD Hf-silicate films could be easily controlled by regulating the number of deposition cycles using Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 and TDMAS ͑SiH͓N͑CH 3 ͒ 2 ͔ 3 ͒, or Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 and BDMAS ͑SiH 2 ͓N͑CH 3 ͒ 2 ͔ 2 ͒ precursors.…”
mentioning
confidence: 99%